Hexagonal-shaped tin glycolate particles: A preliminary study of their suitability as li-ion insertion electrodes - Ng, See-How; Chew, Sau-Yen; dos Santos, Dayse I. [UNESP]; Chen, Jun; Wang, Jia-Zhao; Dou, Shi-Xue; Liu, Hua-Kun (Wiley-v C H Verlag Gmbh, 2008)
Tin glycolate particles were prepared by a simple, one-step, polyol-mediated synthesis in air in which tin oxalate precursor was added to ethylene glycol and heated at reflux. Hexagonal-shaped, micron-sized tin glycolate particles were formed when the solution had cooled. A series of tin oxides was produced by calcination of the synthesized tin glycolate at 600-800 degrees C. It was revealed that the micron-sized, hexagonal-shaped tin glycolate now consisted of nanosized tin-based particles (80-120 nm), encapsulated within a tin glycolate shell. XRD, TGA, and FT-IR measurements were conducted to account for the three-dimensional growth of the tin glycolate particles. When applied as an anode material for Li-ion batteries, the synthesized tin glycolate particles showed good electro-chemical reactivity in Li-ion insertion/ deinsertion, retaining a specific capacity of 416mAhg(-1) beyond 50cycles. Ibis performance was significantly better than those of all the other tin oxides nanoparticles (< 160mAhg(-1)) obtained after heat treatment in air. We strongly believe that the buffering of the volume expansion by the glycolate upon Li-Sn alloying is the main factor for the improved cycling of the electrode.
Keywords: electrochemistry; lithium nanoparticles; tin glycolate